What is your language? - Leventhal, Debra; Wellington, Monica (New York : Dutton Children?s Books, 1994)
Emphasizes that many different languages are spoken in different parts of the world, giving examples from French and German to Arabic and Spanish.
Keywords: Language and languages -- Juvenile literature; Language and languages